다양한 노안교정 방법. - Kim, Jae Yong (Journal of the Korean Medical Association / Taehan Uisa Hyophoe Chi, 2025)
Purpose: Presbyopia refers to the loss of the eye's ability to accommodate and focus on objects at various distances as a person ages, typically starting with difficulty focusing on near objects. The decline in accommodation begins in childhood or the 20s, becomes noticeable in the early 40s, and is almost completely lost by the mid-50s. Symptoms of presbyopia commonly begin in the mid-40s, with patients often complaining of blurred or unclear vision when reading books, newspapers, or other mobile devices. As the condition progresses, individuals may find themselves holding reading material further away to see clearly. They may also experience eye strain, headaches during near work, and increased difficulty reading small print in dim lighting conditions. Current Concepts: The primary causes of presbyopia are the stiffening of the lens, aging of the ciliary muscle and zonules, and changes in the biomechanical properties of the structures involved in accommodation. Methods for correcting presbyopia include both fixed- and variable-focus lens systems, as well as surgical interventions that replace the cataractous lens with a presbyopia-correcting intraocular lens, modify the optics of the cornea with laser treatment, or attempt to at least partially restore active accommodation, with ongoing efforts to improve the presbyopic visual experience. Discussion and Conclusion: Various effective treatment options for presbyopia patients have been developed and implemented, leading to increased patient satisfaction thanks to advanced technologies. However, a personalized approach tailored to each patient's condition is crucial, and long-term data, along with ongoing research, are necessary for further advancements.